Narrative of differences in the recomposition of a file - Álvarez, Verónica (Universidad Nacional del Litoral, 2020)
The following textual body is part of a doctoral research project which proposes a revision of the literary and critical discursive practices of Venezuelan literature of the first half of the 20th century, based on monstrous authorship as a category of reading and interpretation. A conception that reexamines the reflection on the notion of author, which displaces and problematizes. It is a form of authorship in which not only the elaborated aesthetic product matters, but also the own vital attitude of the producer towards and within the literary territory in which it emerges and against which it struggles. These author constellations unmask an «anti-literary» proposal, slightly revised and therefore excluded, that reveals the fissures of an official narrative of the History of Venezuelan Literature. Congregate and analyze these singular and eccentric authorships, in any given cultural field, sketchs definitive traces for the possible elaboration of a counterhistory of Venezuelan literature that will dialogue and complete the official discourses narrated from the hegemonic notion of the literary.